Factors affecting local recurrence and distant metastases of invasive breast cancer after breast-conserving surgery in Chiang Mai university hospital - Chagkrit Ditsatham (2018)
© 2016 Ditsatham et al. Background: The purpose of this study was to collect data regarding breast cancer profiles and factors that affect local recurrence and distant metastasis after breast-conserving surgery (BCS) in Chiang Mai University Hospital. Materials and methods: This study was a retrospective review in a single institution of newly diagnosed invasive breast cancer patients who were treated with BCS between April 9, 2001 and December 25, 2011. Results: A total of 185 patients treated with BCS were included in this study, with an average age of 46.83 years. The average recurrence age was 41.1 years and the average nonrecurrence age was 47.48 years, with a recurrence rate of 10.27%. Premenopause was significant in recurrence (P=0.047), as well as non-estrogen-expression patients (P=0.001) and patients who did not receive antihormonal treatment (P=0.011). Conclusion: The recurrence rate in our institute was 10.27%. Factors affecting recurrence after BCS included young age, premenopausal status, nonexpression of the estrogen receptor, and patients who had not received antihormonal treatment. The recurrence rate was higher in the first 90 postoperative months.